2010
DOI: 10.1590/s1677-55382010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of prostate: a comparison of standard monopolar versus bipolar saline resection

Abstract: Introduction: Transurethral resection syndrome is an uncommon but potentially life threatening complication. Various irrigating solutions have been used, normal saline being the most physiological. The recent availability of bipolar cautery has permitted the use of normal saline irrigation. Material and Methods: In a randomized prospective study, we compared the safety and efficacy of bipolar cautery (using 0.9% normal saline irrigation) versus conventional monopolar cautery (using 1.5% glycine irrigation). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
36
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 13 publications
6
36
2
Order By: Relevance
“…8 In recent years (2009-2013), a number of new RCTs, including multicenter and international studies, have been published. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, it is necessary to conduct a new systematic review and metaanalysis of RCTs that assesses the efficacy and safety (primary outcomes) of M-TURP and B-TURP in patients with BPO.…”
mentioning
confidence: 99%
“…8 In recent years (2009-2013), a number of new RCTs, including multicenter and international studies, have been published. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, it is necessary to conduct a new systematic review and metaanalysis of RCTs that assesses the efficacy and safety (primary outcomes) of M-TURP and B-TURP in patients with BPO.…”
mentioning
confidence: 99%
“…He explained use of non-haemolytic hypoosmolar fluid like glycine has entirely reduced the incidence of TUR syndrome in monopolar TURP cases. Singhania et al (7) in his study had greater decline in serum sodium (4.12 mEq/L) compared to bipolar saline group (1.3 mEq/L); however, this is not statistically significant. He explained that osmolality of the absorbed irrigant is equally responsible for the development of TUR syndrome and not only serum sodium level.…”
Section: Discussionmentioning
confidence: 71%
“…Patankar et al (11) in his study found significant blood loss among patients undergoing monopolar TURP (282.67 mL) as compared to those undergoing bipolar TURP (140.6 mL). Singhania et al (7) in his study showed statistically significant haemoglobin drop (0.97 gm%, p value < 0.005) as compared to bipolar group which showed small drop in haemoglobin (0.55 gm%, p value = 0.014).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations